Titanium-based amorphous brazing filler metal and preparation method thereof

Through the multi-alloyed titanium-based amorphous solder, the lack of performance of traditional solder is solved when connecting to titanium and titanium alloys is achieved, and the coordinated optimization of low-temperature welding, fluidity and strength is achieved, and it is suitable for precision connections in high-end manufacturing fields.

CN119635084APending Publication Date: 2025-03-18YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921258.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When traditional brazing materials are connected to titanium and titanium alloys, there are problems such as poor wetting, poor interface bonding, easy oxidation under high temperature conditions, and insufficient strength and toughness. The welding temperature of existing titanium-based amorphous brazing materials is high and the fluidity is limited.

Method used

The multi-alloyed titanium-based amorphous solder is made of TiaZrbNicCudYeBfLagSih. By accurately selecting and controlling the element composition, the welding temperature is reduced, the fluidity and spreadability are improved, and the welding strength is ensured.

Benefits of technology

It achieves the provision of medium welding strength under low temperature conditions, reduces welding temperature, improves the fluidity and spreadability of the solder, meets the requirements of high-performance connections, and maintains good performance stability under high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208064570000051
    Figure BDA0005208064570000051
  • Figure BDA0005208064570000061
    Figure BDA0005208064570000061
  • Figure HDA0005208064580000011
    Figure HDA0005208064580000011
Patent Text Reader

Abstract

The chemical composition of the titanium-based amorphous brazing filler metal is TiaZrbNicCudYeBfLagSih, and the stoichiometric ratios of all the elements are as follows: 43 < = a < = 77, 20 < = b < = 28, 12 < = c < = 18, 6 < = d < = 13, 0.8 < e < = 1.6, 0.2 < f < = 0.9, 1.0 < g < = 1.6 and 0.3 < h < = 0.9. According to the titanium-based amorphous brazing filler metal, through component regulation and control, comprehensive improvement in the aspects of low-temperature welding, flow wettability and welding strength reliability is successfully achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solder, in particular to a titanium-based amorphous solder and a preparation method thereof. Background Art

[0002] Brazing filler metal is an indispensable key material for connecting metal or non-metal materials, especially in high-end manufacturing fields such as aerospace, medical equipment, electronic manufacturing, and the automotive industry, where its performance is directly related to the reliability, stability, and service life of the connector. Traditional brazing fillers, such as silver-based, copper-based, and nickel-based, although they perform well in certain specific occasions, encounter technical difficulties in connecting with titanium and titanium alloys.

[0003] Titanium and titanium alloys have been widely used in high-end fields such as aerospace, medical equipment, etc. due to their significant advantages such as high strength, light weight, high temperature resistance and corrosion resistance. However, traditional brazing fillers have obvious shortcomings when connecting with titanium and titanium alloys. They have poor wettability with titanium alloys and it is difficult to form a good interface bond, which affects the connection performance. In addition, under high temperature conditions, traditional brazing fillers are prone to oxidation reactions, resulting in degradation of joint performance. At the same time, the strength and toughness of traditional brazing fillers cannot meet the requirements of use in high load and high impact environments. In order to overcome these challenges, researchers have begun to pay attention to amorphous brazing fillers, especially amorphous titanium-based brazing fillers.

[0004] However, the welding temperature of existing titanium-based amorphous solders generally exceeds 950°C. This is because the melting point of most titanium-based solders is above 830°C, which makes the existing titanium-based amorphous solders generally have the risk of overburning. In some special occasions, such as brazing connections of titanium alloy non-structural parts, repair of titanium alloy workpieces, low-temperature secondary welding, etc., the melting point of brazing connections can reach 750°C, which can provide medium welding strength when the welding temperature is less than 850°C. However, titanium-based amorphous solders with lower welding temperatures are rarely reported. At the same time, the existing titanium-based amorphous solders have a solidus and liquidus temperature difference that generally exceeds 100°C. The large melting temperature range makes the fluidity and spreadability of the solder have great limitations. Summary of the invention

[0005] In view of the above problems in the prior art, the present invention provides a multi-alloyed titanium-based amorphous solder having a chemical composition of Ti a Zr b Ni c Cu d Y e B f La g Si hThe stoichiometric ratio of each element is 43≤a≤77, 20≤b≤28, 12≤c≤18, 6≤d≤13, 0.8<e≤1.6, 0.2<f≤0.9, 1.0<g≤1.6, 0.3<h≤0.9.

[0006] In the composition of the titanium-based amorphous solder of the present invention, the welding temperature of the titanium-based amorphous solder is effectively reduced by accurately selecting and regulating the alloying elements, while ensuring the low-temperature fluidity and spreadability of the solder, and the welding strength is effectively guaranteed.

[0007] Among them, titanium (Ti) is the basic element of the alloy, and titanium is the main component element, which ensures that the solder has excellent compatibility with the titanium-based welding object and can maintain good strength and corrosion resistance. Zirconium (Zr) as the first component element cooperates with Ti to play a role in surface tension and enhance its fluidity. Nickel (Ni) as the second component element cooperates with Ti and Zr to improve the mechanical strength and corrosion resistance of the solder. Copper (Cu) is introduced into the above system. On the one hand, it is used together with Ni as a soft metal to match the ductility of the Ti matrix. On the other hand, it preliminarily effectively reduces the melting point of the system, and the melting point and fluidity of the solder are greatly improved. The present invention further deploys the trace element system of YB-La-Si, so that the titanium-based solder further achieves the coordinated optimization of low-temperature welding, fluidity and strength. The addition of yttrium (Y) and boron (B) further refines the microstructure of the solder, improves the strength from the microscopic level, and optimizes the amorphous forming ability of the system on the basis of this microscopic strengthening, with a high degree of amorphization and stable performance. Lanthanum (La) and silicon (Si) can enhance the glass-forming ability of the alloy, further stabilize the amorphization, and synergize with Ni to improve the strength and corrosion resistance of the brazing material.

[0008] As some further preferred solutions, in the chemical composition of titanium-based amorphous solder, 3<f+e+g+h≤5. The total ratio optimization of YB-La-Si improves the overall performance of the solder while ensuring the stability of the amorphous structure. This helps to avoid phase change caused by excessive content, thereby maintaining good comprehensive properties such as toughness, hardness and thermal stability. At the same time, this optimization condition can also effectively control production costs.

[0009] As some further preferred solutions, in the chemical composition of titanium-based amorphous solder, 0.1<f / e≤0.8. This is conducive to balancing the amorphous forming ability and strength of the solder. This helps the solder to form a good amorphous structure while having sufficient strength to meet the mechanical performance requirements in low temperature scenarios, ensuring the reliability of the welded joint.

[0010] As some further preferred solutions, in the chemical composition of titanium-based amorphous solder, 0.2<h / g≤0.8. This further enhances the glass-forming ability of the solder and improves the thermal stability of the alloy. This also helps to ensure that the performance of the solder does not degrade under high-temperature applications and meets the reliability and stability requirements of long-term use.

[0011] As some further preferred schemes, in the chemical composition of titanium-based amorphous solder, the stoichiometric ratio of each element is 43≤a≤60, 22≤b≤26, 12≤c≤18, 6≤d≤10, 1<e≤1.6, 0.4<f≤0.8, 1.2<g≤1.6, 0.4<h≤0.8, 3<f+e+g+h≤5, 0.3<f / e≤0.7, 0.3<h / g≤0.6. The alloying ratio within the optimized range further accurately adjusts the synergistic compatibility between the elemental compositions, so that the solder can achieve a further reduction in welding temperature while ensuring mechanical properties, alloy stability and wetting properties.

[0012] The present invention also provides a method for preparing the above-mentioned titanium-based amorphous solder, comprising mixing metals or intermetallic compounds having a target element composition according to a stoichiometric ratio, and then smelting them at 1500°C to 1600°C under vacuum or protective gas conditions, obtaining a mother ingot after cooling, liquefying the mother ingot under vacuum or protective gas conditions, transferring the liquefied liquid to a carrier and rapidly cooling it to obtain a titanium-based amorphous solder.

[0013] As some further preferred embodiments, the melting, liquefaction and liquefied liquid transfer are carried out in a vacuum environment, and the vacuum pressure is less than 1×10 -4 Pa.

[0014] As some further preferred schemes, after smelting, slowly cooling to room temperature at a rate of <10°C / min is helpful to reduce stress and defects inside the alloy, thereby obtaining a mother ingot with uniform composition and stable quality.

[0015] As some further preferred solutions, the cooling rate of the liquefied liquid on the carrier is 700° C. / s to 1500° C. / s.

[0016] As some further preferred solutions, the choice of the carrier is not limited, and is preferably a metal substrate with a cooling function, such as a water-cooled copper rod, which is conducive to the rapid cooling of the liquefied liquid.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects:

[0018] 1. Good comprehensive performance

[0019] The titanium-based amorphous solder of the present invention exhibits good comprehensive performance through component regulation and optimization. The melting point of the solder is controlled between 740°C and 793°C, which is convenient for brazing operation and ensures that the welding quality is not affected. The shear strength of the joint is above 465MPa, which significantly improves the mechanical properties of the welded joint and meets the strict requirements of high-performance connections. At the same time, the contact angle of the solder on the surface of the amorphous titanium-based strip is less than 20°, showing good wettability, thereby ensuring the quality of the welded joint. And under the further precise adjustment of the element composition, the melting point of the titanium-based amorphous solder can reach 740°C to 765°C, the shear strength is above 480MPa, the wetting angle reaches 15.5°-17.3°, and the comprehensive performance indicators are further improved.

[0020] 2. Excellent stability

[0021] The solder of the present invention can still maintain excellent performance stability in harsh service environments such as high temperature and strong corrosion. This is due to the precise coordination and synergy between the elements, especially the reasonable combination of YB-La-Si, and the carefully designed component ratio. These characteristics make the solder have good corrosion resistance, and the performance degradation phenomenon is not obvious during long-term use, thereby significantly improving the reliability and service life of the product.

[0022] 3. Wide adaptability

[0023] The titanium-based amorphous solder of the present invention can be widely used in connection requirements of various titanium and titanium alloy materials, especially in the field of precision connection in high-end manufacturing industries such as aerospace, medical equipment, and precision electronics. Its excellent performance and stable preparation process make the solder an ideal choice in these fields, making an important contribution to promoting the development and progress of related industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1-3 The following are pictures of the products obtained in Examples 1, 4 and 8 respectively.

[0026] Figure 4 This is the XRD diagram of a typical product of the present invention. DETAILED DESCRIPTION

[0027] Detailed preparation methods and technical steps are provided in the embodiments of the present invention, and are intended to fully illustrate the specific implementation process of the present invention. However, these detailed technical details only represent a specific way to realize the present invention, and are not intended to limit the core content of the present invention or its protection scope. It should be understood by those skilled in the art that these embodiments are only for illustrative purposes and should not be regarded as limiting the only or exclusive implementation mode of the present invention.

[0028] The titanium-based amorphous solder in the present invention is prepared by the following method.

[0029] Raw materials preparation:

[0030] The raw materials used are high-purity metals and their compounds to ensure the purity and performance stability of the solder. The specific composition includes: titanium (Ti), zirconium (Zr), nickel (Ni), copper (Cu), silicon (Si) particles with a purity of not less than 99.95wt%, boron (B) added in the form of 2.52wt% boron-titanium alloy powder, yttrium (Y) added in the form of 1.67wt% yttrium-copper alloy powder, and lanthanum (La) introduced in the form of 1.5wt% nickel-lanthanum alloy particles.

[0031] All raw materials need to be dried at a temperature range of 100°C to 160°C for 24 hours to completely remove moisture and impurities, thereby ensuring the purity and uniformity of the raw materials. The weighing operation is carried out using an electronic balance with an accuracy of 0.0001g, the operating environment temperature is maintained between 20°C and 25°C, and the relative humidity is controlled within the range of 30% to 50%, in order to minimize errors and avoid cross contamination.

[0032] The weighed raw materials must be stored in dry and sealed containers and clearly labeled to prevent confusion and secondary contamination.

[0033] Melting process:

[0034] The pretreated metal raw materials are placed in a vacuum induction melting furnace. First, the furnace is evacuated to a pressure below 1×10 -4 Pa to completely exclude air and prevent oxidation reaction. Then, 100% pure argon is filled as a protective atmosphere to further prevent oxidation and contamination.

[0035] The furnace temperature was raised to 1500℃~1600℃ at a heating rate of 12℃ / min~16℃ / min. This temperature range is conducive to complete melting and uniform mixing of the alloy. This temperature was maintained for 30 minutes to ensure that the alloy composition was fully uniform. During the entire smelting process, the furnace pressure was maintained at less than 1×10 -4Pa level to create an ideal smelting environment. After smelting, slowly cool to room temperature at a rate of 4℃ / min. This cooling rate helps to reduce stress and defects inside the alloy, thereby obtaining a mother ingot with uniform composition and stable quality.

[0036] Rapid cooling to prepare solder:

[0037] The smelted alloy block is placed in a quartz tube, which serves as a container and protective layer during the rapid cooling process. The quartz tube is evacuated again to a pressure below 1×10 -4 Pa, and filled with argon as a protective atmosphere to prevent the alloy from oxidation and contamination during rapid cooling.

[0038] The alloy block is heated to liquid state by medium frequency induction heating. Subsequently, the melt is squeezed out of the quartz tube by high pressure argon gas and dripped continuously onto a water-cooled copper roller rotating at a certain speed. The melt is rapidly cooled on the copper roller to form an alloy strip with an amorphous structure. The cooling rate is controlled between 700℃ / s and 1500℃ / s to ensure the formation and stability of the amorphous structure.

[0039] Through the above method, the present invention prepared specific embodiments and comparative examples according to different stoichiometric ratios, and tested the performance of titanium-based amorphous solders of different embodiments and comparative examples. The results are listed in Table 1 and the accompanying drawings.

[0040] Table 1

[0041]

[0042]

[0043] Examples 1-9 demonstrate that the titanium-based amorphous solder of the present invention has successfully achieved comprehensive improvements in low-temperature welding, flow wettability, and welding strength reliability through the coordinated deployment of elements. Compared with Comparative Examples 6-7, it can be seen that the change in the trace element system fundamentally changes the applicable welding temperature range of the titanium-based amorphous solder. At the same time, Comparative Examples 1-5 demonstrate that the precise regulation of the content of each element is also the key to ensuring the balance of welding temperature, strength, and wettability. The titanium-based amorphous solder of the present invention can reach a wetting angle of less than 20° at a temperature between 740°C and 793°C, a joint shear strength of more than 465MPa.

[0044] Figure 1-3 The actual product pictures obtained in Examples 1, 4 and 8 are shown respectively, and it can be seen that the titanium-based amorphous solder of the present invention is formed into an alloy strip shape, has good thinness and flexibility, and can be widely used in welding requirements between different structural relationships. Figure 4The XRD patterns of the products obtained in Example 3 of the present invention and Comparative Example 5 are shown, and it can be seen that the present invention (Example 3) has a good amorphous alloy phase, while changing the element composition (Comparative Example 5) not only causes changes in the comprehensive performance, but also causes a small amount of crystallization peaks to appear in the amorphous system, indicating that the stability of the amorphous system is also adversely affected.

[0045] By observing Examples 1-9, it can be found that the solidus, liquidus, melting point, glass transition temperature, joint shear strength and wetting angle of the titanium-based amorphous solder are all correlated with the relative changes in the composition of each element, but they do not completely show a single regular change. It can be seen that the relative ratio between the elements has an unpredictable impact on the internal mechanisms such as the microstructure, thermal transition behavior, atomic diffusion, and chemical bond connection of the material. When it exceeds a certain reasonable range, the mechanical properties of the welded joint will be weakened, resulting in defects at the joint, poor interface bonding, or uneven microstructure, which are not conducive to resisting shear force.

[0046] It can be seen from Examples 1, 2, 4, and 7 relative to Examples 3, 5, 6, 8, and 9 that the further precisely adjusted element composition further improves the comprehensive performance indicators, the melting point of the material can reach 740°C to 765°C, the shear strength can reach more than 480MPa, and the wetting angle can reach 15.5°-17.3°.

[0047] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A titanium-based amorphous solder, the chemical composition of which is Ti a Zr b Ni c Cu d Y e B f La g Si h The stoichiometric ratio of each element is 43≤a≤77, 20≤b≤28, 12≤c≤18, 6≤d≤13, 0.8<e≤1.6, 0.2<f≤0.9, 1.0<g≤1.6, 0.3<h≤0.

9.

2. The titanium-based amorphous solder according to claim 1, characterized in that: In the chemical composition of titanium-based amorphous solder, 3<f+e+g+h≤5.

3. The titanium-based amorphous solder according to claim 1, characterized in that: In the chemical composition of titanium-based amorphous solder, 0.1<f / e≤0.

8.

4. The titanium-based amorphous solder according to claim 1, characterized in that: In the chemical composition of titanium-based amorphous solder, 0.2<h / g≤0.

8.

5. The titanium-based amorphous solder according to claim 1, characterized in that: In the chemical composition of titanium-based amorphous solder, the stoichiometric ratio of each element is 43≤a≤60, 22≤b≤26, 12≤c≤18, 6≤d≤10, 1<e≤1.6, 0.4<f≤0.8, 1.2<g≤1.6, 0.4<h≤0.8, 3<f+e+g+h≤5, 0.3<f / e≤0.7, 0.3<h / g≤0.

6.

6. A method for preparing the titanium-based amorphous solder according to any one of claims 1 to 6, comprising mixing metals or intermetallic compounds having a target elemental composition in a stoichiometric ratio, then smelting them at 1500°C to 1600°C under vacuum or protective gas conditions, obtaining a mother ingot after cooling, liquefying the mother ingot under vacuum or protective gas conditions, transferring the liquefied liquid to a carrier and rapidly cooling it to obtain a titanium-based amorphous solder.

7. The method for preparing titanium-based amorphous solder according to claim 6, characterized in that: Melting, liquefaction and liquefied liquid transfer are carried out in a vacuum environment with a vacuum pressure of less than 1×10 -4 Pa.

8. The method for preparing titanium-based amorphous solder according to claim 6, characterized in that: After melting, it was slowly cooled to room temperature at a rate of <10°C / min.

9. The method for preparing titanium-based amorphous solder according to claim 6, characterized in that: The cooling rate of the liquefied liquid on the carrier is 700° C. / s to 1500° C. / s.

10. The method for preparing the titanium-based amorphous solder according to claim 6, characterized in that: The carrier is a metal matrix with cooling function.